Role of ErbB/HER family of receptor tyrosine kinases in cholangiocyte biology. Issue 2 (26th December 2017) - Pellat, Anna; Vaquero, Javier; Fouassier, Laura
Abstract : The ErbB/HER family comprises four distinct tyrosine kinase receptors, EGFR/ErbB1/HER1, ErbB2/HER2, ErbB3/HER3, and ErbB4/HER4, which trigger intracellular signals at the origin of essential cellular functions, including differentiation, proliferation, survival, and migration. Epithelial cells, named cholangiocytes, that line intrahepatic and extrahepatic bile ducts, contribute substantially to biliary secretory functions and bile transport. Although ErbB receptors have been widely studied in cholangiocarcinoma (CCA), a malignancy of the biliary tract, knowledge of these receptors in biliary epithelium physiology and in non‐malignant cholangiopathies is far from complete. Current knowledge suggests a role for epidermal growth factor receptor (EGFR) in cholangiocyte specification and proliferation, and in hepatocyte transdifferentiation into cholangiocytes during liver regeneration to restore biliary epithelium integrity. High expression and activation of EGFR and/or ErbB2 were recently demonstrated in biliary lithiasis and primary sclerosing cholangitis, two cholangiopathies regarded as risk factors for CCA. In CCA, ErbB receptors are frequently overexpressed, leading to tumor progression and low prognosis. Anti‐ErbB therapies were efficient only in preclinical trials and have suggested the existence of resistance mechanisms with the need to identify predictive factors of therapy response. This review aims to compile the current knowledge on the functions of ErbB receptors in physiology and physiopathology of the biliary epithelium. (Hepatology 2018;67:762‐773).